The relation between SARS-CoV-2 cases in Bahrain and meteorological parameters: 27 months of data - Alnaser, Waheeb E.; Alnaser, Naser W.; Almarabheh, Amer J.; Al-Ansari, Ahmed M.; Al-Aali, Hala H.; Ghanem, Amjad Z. (Frontiers in Built Environment, 2022)
There is a strong thought that meteorological parameters affect the spread of SARS-CoV-2. Many studies have been conducted in this regard, but were based on a short time period of investigation. Herein, this relation is studied based on 27 months of recorded data pertaining to SARS-CoV-2. The analyzed data includes official recorded data of SARS-CoV-2 cases in Bahrain, starting from 24 February 2020 - when the first case of SARS-CoV-2 was detected - until 18 May 2022. The analyzed data also includes four meteorological parameters (temperature, wind speed, relative humidity and absolute humidity). The data was analyzed using SPSS, with P-value less than 0.05 was considered as statistically significant. There is a negative significant correlation between daily new cases of SARS-CoV-2 and temperature, T, and absolute humidity, AH, (r = -0.290, -0.317; P < 0.001, respectively). The results also show a positive significant correlation between daily cases of SARS-CoV-2 and wind speed, V, (r = -0.110; P =0.002). There is no correlation between daily cases of SARS-CoV-2 and relative humidity (r = -0.028; P = 0.429). An empirical relation is reported, allowing the estimation of SARS-CoV-2 cases in Bahrain as a function of three weather parameters T, AH and V. Sustainable Design and construction must consider such a relation in order to minimize the overwhelming spread of viruses and the subsequent illness.